(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Due to the complexity of adhesion and irregularity of human umbilical vein endothelial cells, we propose a novel cell image segmentation technique by combining cell image with corresponding nucleus image based on label-controlled watershed algorithm instead of segmenting the cell image directly. Moreover, nucleus segmentation and location in stained cells are introduced. The most fascinating advantage of the combined method is its accurate positioning, which ensures that the center of each cell could be positioned accurately and is conducive to the adhesion and irregular cells segmentation. To determine the activation time of nuclear factor kappa B and its signaling pathway blocking mechanism, relevant fluorescence parameters extraction approach is also discussed. Performance and result analysis demonstrate that this algorithm is valid, precise, and very helpful to further cell analysis and medical diagnosis.